The role of nutritional support in treatment of head and neck tumors: clinical case - A. M. Mudunov; M. B. Pak; L. Ya. Wolf (Опухоли головы и шеи)
The article presents a clinical observation of treatment of locally advanced squamous cell oropharyngeal carcinoma. The problems of nutritional support of patients during primary chemoradiation treatment are considered. The presented clinical case shows that use of sip feeds can significantly improve nutritional condition in patients with head and neck tumors and improve tolerability and results of antitumor treatment.